The Relationship between School Administrators’ Leadership Traits and Learning Schools: A Meta-Analysis Study - Alanoglu, Muslim; Karabatak, Songul (Ozgen Korkmaz, 2021)
School administrators’ leadership characteristics are crucial in creating a learning school. Therefore, this study aimed to examine the relationship between transformational leadership characteristics and the learning school using meta-analysis. For this purpose, individual studies suitable for inclusion criteria were determined. In this context, we examined the studies between the years 2000 and 2020 on the relationship between school administrators’ transformational leadership characteristics and learning schools. Studies including correlation coefficient, t value, and sample size were covered to calculate the effect size required for metaanalysis. A total of 20 effect sizes were included in the 19 studies. In the study, analyses of forest plots, publication bias, heterogeneity, and subgroup tests were performed. The random-effects model conducted in the study determined that the overall effect size was positive and strong. The subgroup analysis showed that the country variable was the source of heterogeneity in effect sizes, while the publication type was not. The study revealed that leadership characteristics are significant predictors of learning school and one of the most critical leadership styles to create a learning school is transformational leadership. Policymakers and practitioners have essential duties in transforming schools into learning schools. Therefore, school administrators who want to turn their schools into learning organizations should always be supported by those who produce education policies. © 2021, Ozgen Korkmaz. All rights reserved.
Keywords: Learning school; Meta-analysis; School administrator; Transformational leadership